Vacuolar proteases and autophagy in phytopathogenic fungi: A review - Juárez-Montiel, Margarita; Clark-Flores, Daniel; Tesillo-Moreno, Pedro; de la Vega-Camarillo, Esaú; Andrade-Pavón, Dulce; Hernández-García, Juan Alfredo; Hernández-Rodríguez, César; Villa-Tanaca, Lourdes (Frontiers in Fungal Biology, 2022)
Autophagy (macroautophagy) is a survival and virulence mechanism of different eukaryotic pathogens. Autophagosomes sequester cytosolic material and organelles, then fuse with or enter into the vacuole or lysosome (the lytic compartment of most fungal/plant cells and many animal cells, respectively). Subsequent degradation of cargoes delivered to the vacuole via autophagy and endocytosis maintains cellular homeostasis and survival in conditions of stress, cellular differentiation, and development. PrA and PrB are vacuolar aspartyl and serine endoproteases, respectively, that participate in the autophagy of fungi and contribute to the pathogenicity of phytopathogens. Whereas the levels of vacuolar proteases are regulated by the expression of the genes encoding them (e.g., PEP4 for PrA and PRB1 for PrB), their activity is governed by endogenous inhibitors. The aim of the current contribution is to review the main characteristics, regulation, and role of vacuolar soluble endoproteases and Atg proteins in the process of autophagy and the pathogenesis of three fungal phytopathogens: Ustilago maydis, Magnaporthe oryzae, and Alternaria alternata. Aspartyl and serine proteases are known to participate in autophagy in these fungi by degrading autophagic bodies. However, the gene responsible for encoding the vacuolar serine protease of U. maydis has yet to be identified. Based on in silico analysis, this U. maydis gene is proposed to be orthologous to the Saccharomyces cerevisiae genes PRB1 and PBI2, known to encode the principal protease involved in the degradation of autophagic bodies and its inhibitor, respectively. In fungi that interact with plants, whether phytopathogenic or mycorrhizal, autophagy is a conserved cellular degradation process regulated through the TOR, PKA, and SNF1 pathways by ATG proteins and vacuolar proteases. Autophagy plays a preponderant role in the recycling of cell components as well as in the fungus-plant interaction.